Representasi Trauma Novel “Aku Tak Membenci Hujan” Karya Sri Puji Hartini: Kajian Psikologi Sastra Cathy Caruth - Malika Zuhrotun Nisak; Syamsul Sodiq (Jurnal Ilmu Bahasa, Sastra, dan Budaya, 2026)
This study aims to describe the forms of trauma experienced by the character Karang and the development process of the trauma until the process of walking through. The method used in this study is a qualitative descriptive method. The research data source is the novel "Aku Tak Memenang Hujan" by Sri Puji Hartini, while the research data are in the form of narrative excerpts and dialogues that indicate the traumatic experience of the character Karang. Data collection techniques were carried out through two main techniques, namely documentation and listening and taking notes. The data analysis technique used in this study is the content analysis technique. The results of the study show that the character Karang experienced trauma and developed through several interrelated forms. These forms of trauma include intrusive thoughts, avoidance, and self-defense (hyperarousal), then there is a process of walking through as a form of self-acceptance. This study shows that trauma not only has a psychological impact on individuals, but also influences how individuals understand themselves and their surroundings. The trauma experienced by the character Karang develops gradually until it leads to a process of recovery.